PEMIKIRAN KRITIS JOHN DEWEY TENTANG PENDIDIKAN - Hasbullah, Hasbullah (UIN Antasari Banjarmasin, 2020)
ABSTRACT: John Dewey's thoughts in the field of education have inspired many thinkers and practitioners of modern education today, apart from Dewey's controversial thoughts that invite pros and cons. In presenting his various ideas as well, Dewey always put forward very argumentative rational reasons. His international reputation lies in his contribution to the educational philosophy of